2014
DOI: 10.3389/fncir.2014.00057
|View full text |Cite
|
Sign up to set email alerts
|

Severe drug-induced repetitive behaviors and striatal overexpression of VAChT in ChAT-ChR2-EYFP BAC transgenic mice

Abstract: In drug users, drug-related cues alone can induce dopamine release in the dorsal striatum. Instructive cues activate inputs to the striatum from both dopaminergic and cholinergic neurons, which are thought to work together to support motor learning and motivated behaviors. Imbalances in these neuromodulatory influences can impair normal action selection and might thus contribute to pathologically repetitive and compulsive behaviors such as drug addiction. Dopamine and acetylcholine can have either antagonistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 93 publications
5
68
0
1
Order By: Relevance
“…Specifically, using CalDAG-GEFI-EGFP mice to visualize matrix neurons, Crittenden and colleagues demonstrated that optogenetic stimulation of CINs disrupts the firing patterns of SPNs in ex vivo striatal slices in a nAChR-dependent way, although the dependence upon GABA remains unclear. This, along with observations that (a) destruction of striatal CINs (and somatostatinergic interneurons) prevents the above drug-induced striosome/matrix pattern of cFos induction, (b) pharmacological blockade of striatal cholinergic signaling increases drug-induced stereotypies, and (c) globally elevating acetylcholine release also exacerbates drug-induced stereotypies(Aliane, Perez, Bohren, Deniau, & Kemel, 2011;Crittenden et al, 2014;Janickova, Prado, Prado, El Mestikawy, & Bernard, 2017;Saka, Iadarola, Fitzgerald, & Graybiel, 2002; see also the preprint byCrittenden et al, deposited in bioRxiv on July 22, 2019 https ://www.biorx iv.org/conte nt/10.1101/709246v1), suggests that a precise balance of striatal cholinergic signaling may be required to shape striosome-linked behaviors and prevent pathological stereotypy. This, along with observations that (a) destruction of striatal CINs (and somatostatinergic interneurons) prevents the above drug-induced striosome/matrix pattern of cFos induction, (b) pharmacological blockade of striatal cholinergic signaling increases drug-induced stereotypies, and (c) globally elevating acetylcholine release also exacerbates drug-induced stereotypies(Aliane, Perez, Bohren, Deniau, & Kemel, 2011;Crittenden et al, 2014;Janickova, Prado, Prado, El Mestikawy, & Bernard, 2017;Saka, Iadarola, Fitzgerald, & Graybiel, 2002; see also the preprint byCrittenden et al, deposited in bioRxiv on July 22, 2019 https ://www.biorx iv.org/conte nt/10.1101/709246v1), suggests that a precise balance of striatal cholinergic signaling may be required to shape striosome-linked behaviors and prevent pathological stereotypy.…”
mentioning
confidence: 65%
“…Specifically, using CalDAG-GEFI-EGFP mice to visualize matrix neurons, Crittenden and colleagues demonstrated that optogenetic stimulation of CINs disrupts the firing patterns of SPNs in ex vivo striatal slices in a nAChR-dependent way, although the dependence upon GABA remains unclear. This, along with observations that (a) destruction of striatal CINs (and somatostatinergic interneurons) prevents the above drug-induced striosome/matrix pattern of cFos induction, (b) pharmacological blockade of striatal cholinergic signaling increases drug-induced stereotypies, and (c) globally elevating acetylcholine release also exacerbates drug-induced stereotypies(Aliane, Perez, Bohren, Deniau, & Kemel, 2011;Crittenden et al, 2014;Janickova, Prado, Prado, El Mestikawy, & Bernard, 2017;Saka, Iadarola, Fitzgerald, & Graybiel, 2002; see also the preprint byCrittenden et al, deposited in bioRxiv on July 22, 2019 https ://www.biorx iv.org/conte nt/10.1101/709246v1), suggests that a precise balance of striatal cholinergic signaling may be required to shape striosome-linked behaviors and prevent pathological stereotypy. This, along with observations that (a) destruction of striatal CINs (and somatostatinergic interneurons) prevents the above drug-induced striosome/matrix pattern of cFos induction, (b) pharmacological blockade of striatal cholinergic signaling increases drug-induced stereotypies, and (c) globally elevating acetylcholine release also exacerbates drug-induced stereotypies(Aliane, Perez, Bohren, Deniau, & Kemel, 2011;Crittenden et al, 2014;Janickova, Prado, Prado, El Mestikawy, & Bernard, 2017;Saka, Iadarola, Fitzgerald, & Graybiel, 2002; see also the preprint byCrittenden et al, deposited in bioRxiv on July 22, 2019 https ://www.biorx iv.org/conte nt/10.1101/709246v1), suggests that a precise balance of striatal cholinergic signaling may be required to shape striosome-linked behaviors and prevent pathological stereotypy.…”
mentioning
confidence: 65%
“…In addition, we used a BAC-trimming approach to remove a nearby gene in the BAC clone to avoid undesirable overexpression of this gene (Ting and Feng, 2014). This is an important step that has not been carried out in previously generated BAC transgenic mice and has resulted in lines with potential confounding and unintended overexpression of unwanted genes (Kolisnyk et al, 2013, Crittenden et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests that cholinergic interneurons in the striatum can exert powerful control over the intrastriatal release of dopamine (34,35). We have noted that these cholinergic interneurons, although having predominant distributions at the striosome-matrix compartment borders (36), send many fine fibers into the striosomes (37,38). By contrast, cholinergic inputs from the brainstem pedunculopontine nucleus (PPN) preferentially innervate the matrix (39).…”
Section: Discussionmentioning
confidence: 99%